2012
DOI: 10.1158/1541-7786.mcr-11-0332
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Cells and Normal Pancreatic Duct Epithelial Cells Express an Autocrine Catecholamine Loop that Is Activated by Nicotinic Acetylcholine Receptors α3, α5, and α7

Abstract: Pancreatic cancer is the fourth leading cause of cancer deaths in developed countries. Smoking is an established risk factor for this malignancy but the underlying mechanisms are poorly understood. Previous reports have provided evidence that nicotinic acetylcholine receptors (nAChRs) and beta-adrenergic receptors (β-ARs) stimulate the growth and migration of pancreatic cancer cells. But a potential cooperation of these two receptor families in the regulation of pancreatic cancer has not been studied to date. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
116
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 38 publications
11
116
0
Order By: Relevance
“…the same as previous studies on other types of cancer such as lung, breast, and pancreatic cancers (17,23,35). Moreover, our study found that increased expression of pAkt was observed within 30 minutes in a time-dependent manner at a dose of 10 mmol/L of nicotine (data not shown).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…the same as previous studies on other types of cancer such as lung, breast, and pancreatic cancers (17,23,35). Moreover, our study found that increased expression of pAkt was observed within 30 minutes in a time-dependent manner at a dose of 10 mmol/L of nicotine (data not shown).…”
Section: Discussionsupporting
confidence: 91%
“…We focused on the a7-nAChR, which is highly associated with tumor growth and cancer progression in other types of cancer (23)(24)(25), and found that at least a7-nAChR was expressed in T24 cells (data not shown). As shown in Fig.…”
Section: Nicotine Promotes Cell Proliferation and Increases Pakt And mentioning
confidence: 99%
“…These promising results suggest that the sympathetic neurotransmitter NE is a bridge connecting the signaling interactions between sympathetic nerves and tumor cells by the molecules NGF and MMPs. It has been shown that pancreatic cancer cells produce their own norepinephrine and epinephrine and that both agents stimulate cell proliferation and invasion by b-adrenergic signaling in an autocrine fashion (40). Given the cross-talk between sympathetic nerves and tumor cells, it is likely that NE produced by tumor cells may be involved in PNI progression, and inhibition of the activity of sympathetic nerves may reduce the PNI in pancreatic cancer, which awaits further experimental validation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, work from Al-Wadei and colleagues demonstrated that stimulation of normal pancreatic duct epithelial cells by nicotine could induce production of catecholamines [41]. Activation of adrenergic receptors by autocrine signaling on non-transformed cells resulted in increased cell proliferation and activation of oncogenic proteins including epithelial growth factor receptor (EGFR).…”
Section: Stress and Cancermentioning
confidence: 99%